Stereotactic Body Radiation Therapy for Low- and Low-Intermediate-Risk Prostate Cancer: Is there a Dose Effect? - Katz, Alan J.; Ashley, Richard; Santoro, Michael; Diblasio, Ferdinand (Frontiers in Oncology, 2011)
This study examines the efficacy and toxicity of two stereotactic body radiation therapy (SBRT) dose regimens for treatment of early prostate cancer. Forty-one patients treated with 35 Gy were matched with 41 patients treated with 36.25 Gy. Both patient groups received SBRT in 5 fractions over 5 consecutive days using the CyberKnife. Each group had 37 low-risk patients and 4 intermediate-risk patients. No statistically significant differences were present for age, prostate volume, PSA, Gleason score, stage, or risk between the groups. The dose was prescribed to the 83-87% isodose line to cover the prostate and a 5-mm margin all around, except 3 mm posteriorly. The overall median follow-up is 51 months (range, 45-58 months) with a median 54 months and 48 months follow-up for the 35-Gy and 36.25-Gy dose groups, respectively. One biochemical failure occurred in each group yielding a 97.5% freedom from biochemical failure. The PSA response has been favorable for all patients with a mean PSA of 0.1 ng/ml at 4-years. Overall toxicity has been mild with 5% late grade 2 rectal toxicity in both dose groups. Late grade 1 urinary toxicity was equivalent between groups; grade 2 urinary toxicity was 5% (2/41 patients) and 10% (4/41 patients) in the 35-Gy and 36.25-Gy dose groups (p = 0.6969), respectively. Overall, the highly favorable PSA response, limited biochemical failures, limited toxicity, and limited impact on quality of life in these low- to low-intermediate-risk patients are supportive of excellent long-term results for CyberKnife delivered SBRT.